PERCEPTIONS OF COOPERATING TEACHERS ON PRE-SERVICE TEACHERS’ MENTORING IN TEACHING PRACTICUM: EMPIRICAL EVIDENCE FROM INITIAL TEACHER EDUCATION - Nurhadi, Kardi; Aryani , Siska (EDUCATIONE, 2024)
Although research on cooperating teachers mentoring pre-service teachers provides important findings in teacher education, there are few studies exploring cooperating teachers' perceptions of mentoring pre-service teachers in Indonesian teacher education. Grounded in narrative inquiry design, this research reports on cooperating teachers' perceptions of mentoring their pre-service teachers during teaching practicum. Two cooperating teachers voluntarily agreed to participate in this study. Data were derived from semi-structured interviews focusing on exploring critical incidents while they were mentoring pre-service teachers. The data were analysed qualitatively using thematic analysis. Findings revealed that pre-service teachers faced difficulties in using English to teach students. However, they benefited from applying strategies and media in their teaching. In terms of mentoring aspects, pre-service teachers were often unprepared with lesson plans, although their communication during teaching practicum was good. To better understand teaching material, pre-service teachers need to enhance their abilities. In addition, pre-service teachers have a limitation in reviewing material and assigning homework, and they struggled to manage class time effectively, leaving insufficient time to review material. This study implied that identifying the challenges faced by pre-service teachers during teaching practicum, as perceived by cooperating teachers, can inform the design of mentoring programs.